ANALYSIS OF CHANGES IN THE SECTORAL ECONOMIC STRUCTURE THROUGH CALCULATION OF AMBON CITY STRUCTURAL CHANGE INDEX IN 2015-2020 - Desry Jonelda Louhenapessy (Jurnal Cita Ekonomika, 2021)
By using the Structural Change Index, this study aims to analyze changes in the economic structure of Ambon City for period 2015-2020. From this analysis it can be concluded; Based on the calculation of the Structural Change index, there has been a change in the economic structure of Ambon City which is marked by the shift in the contribution of the primary sector to the secondary and tertiary sectors in the Ambon City economy. The change by a sectoral shift from the primary sector to the secondary sector to the tertiary sector with an index of 0.64 percent, this means 0.64 percent of economic resources are allocated between sectors, where the tertiary sector develops faster than the primary and secondary sectors by using 0,64 percent of the total sectoral output in Ambon City.